Perancangan Sistem Pengolahan Air Gambut untuk Meningkatkan Ketersediaan Air Bersih - Dhymas Sulistyono Putro; Achmad Imam Santoso; Sri Muliani Agustina; Alicia Wafiq Nur Azizah (Jurnal Serambi Engineering, 2023)
AbstractOne effort that can be done to increase the quantity of clean water is a water treatment system. So that the resulting water quality results can reach PP No. 22 Tahun 2021 quality standards, the resulting water quality results must have an appropriate treatment system to improve the quality of peat water and increase clean water availability. Manufacturing of tools and trials at the Laboratorium Teknik Lingkungan Universitas Muhammadiyah Palangkaraya and collecting peat water on the Palangkaraya Cross-City road. The type of sample used in the implementation of this research is a grab sample, namely a sample taken directly from the water to be monitored. Peat water samples were taken as much as 10 liters. The water treatment system consists of 3 tanks which have their respective functions. Where the first tub is the coagulation tub, the second is the flocculation tub and the third is the filtering tub. The time needed to process peat water into 10 liters of clean water takes about ± 15 minutes. Clean water treatment of 10 liters for 15 minutes can be used by 2-3 people in one treatment. The quantity of water produced by this water treatment device is physically usable, as seen from the efficiency of the time it takes to process 15 minutes in 10 liters so that it can be used for hand washing activities.Keywords: Clean water, peat water, treatment system, time and volume efficiency